"I'll do it in my own class": novice language teacher identity construction in Turkey. Issue 3 (3rd July 2021) - Goktepe, Fatma Tokoz; Kunt, Naciye
ABSTRACT: This paper reports a longitudinal case study exploring the identity construction of a novice English as a Foreign Language (EFL) teacher in Turkey. The study applies sociocultural and post-structural approaches to teacher education and identity formation. It traces the teacher's experiences of becoming and being a teacher drawing upon her reflective teaching narratives, her teaching diary, semi-structured interviews, and the researchers' observation notes. The findings suggest that some features of the induction programmes may negatively affect the novice teachers' construction of a language teacher identity (LTI). Specifically, the negative effect is due to not allowing trainees to experiment or apply their pedagogical perspective in the classroom, or to participate in the classroom on equal levels with their mentor-teachers. The study presents a model that explicates how the LTIs of novice teachers shift from being an imagined to an imposed identity shaped by various constructs: beliefs about teaching and learning, pre-service education, dynamic relations in communities of practice, and contextual factors. The implications for further research are discussed to address LTI construction in EFL contexts.